Theory and method in higher education research. - Huisman, Jeroen; Tight, Malcolm (Emerald Publishing Limited, 2017)
Theory and Method in Higher Education Research provides a forum specifically for higher education researchers to discuss issues of theory and method. This latest collection includes discussion of a variety of theories, including; complex systems theory, organisational identity, curriculum theory, knowledge management framework, evaluation-based decision-making, and the market-university. It also includes a number of chapters focused on methods, including mixed methods and virtual ethnography, as well as a chapter situated between theory and method on the network paradigm. This latest volume presents a truly international approach with contributions from Argentina, Belgium, Canada, the Czech Republic, Finland, Germany, Norway, Portugal, the U.K. and the U.S. to provide an important contribution to international debates regarding the application and development of theory and methodology in researching higher education that will be relevant to researchers globally.